Protective Effects of Anthocyanins from Coreopsis tinctoria against Oxidative Stress Induced by Hydrogen Peroxide in MIN6 Cells. Issue 2 (22nd January 2020) - Liu, Jianli; Tian, Siqi; Fu, Mingyang; He, Yin; Yu, Hui; Cao, Xiangyu; Cao, Yiyang; Xu, Hanyuan
Abstract: Anthocyanins (AC) from Coreopsis tinctoria possesses strong antioxidant properties, while the effects of AC on cells damage induced by reactive oxygen species (ROS) in diabetes mellitus diseases progression have not been reported. The present study was carried out to evaluate the protective property of AC against cellular oxidative stress with an experimental model, H2 O2 ‐exposed MIN6 cells. AC could reverse the decrease of cell viability induced by H2 O2 and efficiently suppressed cellular ROS production and cell apoptosis. In addition, Real‐time PCR and Western blot analyses indicated that AC could protect MIN6 cells against oxidative injury through increasing the translocation of Nrf2 into nuclear, decreasing the phosphorylation level of p38 and up‐regulating the protein expression of antioxidant enzyme (SOD1, SOD2 and CAT). Thus, this study provides evidence to support the beneficial effect of AC in inhibiting MIN6 cells from H2 O2 ‐induced oxidative injury. Abstract :